Ūʺ Ba Chve e* Ba māʹ toʻ lhanʻ reʺ nhaṅʻʹ Ba māʹ lupʻ sāʺ lū thu - Ba Chve, Ūʺ (Praññʻ sūʹ Cā pe Tuikʻ, 1955)
Economic policy and the working class of Burma; transcript of speeches of the former Burmese minister for mines and defence, and the chairman of the federation of trade unions in Burma, delivered during 1951-1954.